Gender Justice in Inheritance Distribution Practices in South Aceh, Indonesia - Harnides, Harnides; Abbas, Syahrizal; Hasballah, Khairuddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This paper explores the practices of inheritance distribution among the people of South Aceh who commonly divide inheritance property based on customary inheritance law. Heirs receive their shares of inheritance not according to Islamic law (furudh al-muqaddarah), as both male and female heirs earn equal portions. The study of this paper aims to examine the concept of Islamic inheritance law from the perspective of gender equity, the pattern of interaction and formation of customary inheritance law in social institutions, and the basis for the community beliefs in dividing inheritance according to the custom and culture of South Aceh. The study obtained data by observing the practices of inheritance distribution in South Aceh and conducting in-depth interviews with the community figures, the representatives of Ulema Consultative Assembly (Majelis Permusyawaratan Ulama/MPU), and the judges at the Tapaktuan Sharia Court using an empirical juridical approach. The results of the study revealed that the concept of Islamic inheritance law has been an alternative and in line with the principle of gender justice for women in South Aceh as a manifestation of the principle of balanced justice. This principle has been reflected in the patterns of inheritance distribution through the respective customary law mechanisms in accordance with the agreement of all heirs. The people in South Aceh have preferred to divide inheritance through the customary law as it has been more flexible and taken into account the socio-economic conditions and values developed in their community.